Interdisciplinary Approaches to Culture Theory - Kannike, Anu; Pärn, Katre; Tasa, Monika (Approaches to Culture Theory, 2020)
The central theme of the volume is interdisciplinary experimentation. The volume includes collaborative and interdisciplinary studies on a variety of topics, from territorialisation of theory, relations between culture theory and research methodology, culture-dependent meaning formation, power relations in discourses on religion, communal heritage management, celebration practices of (national) holidays, conceptual boundaries of the 'unnatural', temporal boundaries in culture and cultural boundaries within archaeological material. Some of the chapters are dedicated to more general theoretical and methodological questions, while the majority of chapters use Estonian culture as source material for approaching broader cultural theoretical notions and questions. The chapters are the outcome of an experimental collaborative project aimed at bringing together representatives of various disciplines in order to find new ways to conceptualise and study their research objects or discover new study objects between disciplines. The approaches to interdisciplinary collaboration taken by the authors of the chapters are diverse. Some of them juxtapose or combine several disciplinary perspectives on common issue in order to highlight the multifaceted nature that escapes the purview of any one discipline. Some reveal similarities or complementarities between the disciplines despite the apparent differences in their metalanguage and theoretical apparatus. Others take a more integrative approach and aim to present a more holistic interdisciplinary theoretical or methodological framework. Several of the chapters re-evaluate or re-interpret existing data or case studies from the vantage points afforded by other fields, prompting questions that are not usually asked within their own field. In addition, the experimental collaboration also offered a space within which to explore issues located between disciplines and whose reoccurring presence becomes evident when diverse disciplines and studies are brought into dialogue.